The use and influence of structural transformation research by policymakers, development agencies and academics. - CGIAR Research Program on Policies, Institutions, and Markets (2017)
Research conducted on Structural Transformation (ST) has had a significant global influence with policymakers, development agencies and academics. The work has appeared in a DFID Economic Development Strategy, AGRA’s 2017 Africa Agriculture Status Report, in a series of UNECA country profiles, and in the Economist and Monthly Digest of the National Bureau of Economic Research. The work was selected by ODI as an impact case study at the request of DFID, which concludes that it had significant policy impact.